2022
DOI: 10.32996/jmhs.2022.3.3.5
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Infant Prematurity and Parental Anxiety: A Systematic Review

Abstract: Prematurity refers to the birth of a baby before 37 completed weeks of pregnancy. This can be related to considerable parental anxiety and mental status changes. Anxiety can manifest as worrying thoughts, feelings of tension, and altered vital signs. This review aims to analyze the relationship between premature birth and parental anxiety, focusing on the emotional status of both mothers and fathers. The review was performed using the Preferred Reporting Items for Systematic Reviews and Meta-Analysis 2020 guid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…The subgroup with very high anxiety scores is the most vulnerable and at risk for long-term sequelae. Previous adult and neonatal studies reported similar findings [20][21][22]. Nurses in adult ICUs poorly assessed stress and anxiety in their patients [20,21].…”
Section: Discussionsupporting
confidence: 62%
“…The subgroup with very high anxiety scores is the most vulnerable and at risk for long-term sequelae. Previous adult and neonatal studies reported similar findings [20][21][22]. Nurses in adult ICUs poorly assessed stress and anxiety in their patients [20,21].…”
Section: Discussionsupporting
confidence: 62%
“…A substantial body of literature suggests that preterm birth is a significant risk factor for the occurrence of postpartum disorders in mothers. 1,2 Mothers of preterm infants report more postpartum psychological problems than other mothers. 3 These mothers experience premature birth as a bodily phenomenon: it is a perinatal complication that poses life-threatening risks for them, 4 as well as for their babies.…”
Section: Introductionmentioning
confidence: 99%
“…When delivery occurs before the 37th week of amenorrhea, the birth is considered to be premature. A substantial body of literature suggests that preterm birth is a significant risk factor for the occurrence of postpartum disorders in mothers 1,2 . Mothers of preterm infants report more postpartum psychological problems than other mothers 3 .…”
Section: Introductionmentioning
confidence: 99%